Analysis of Risk Factors for Acute Respiratory Infections (ARI) in Children Under Five - Tangdilian, Roberth; Azis, Rahmawati; Ningsih, Nining Ade (Jurnal Keperawatan Profesional (KEPO), 2025)
Acute Respiratory Infections (ARI) are a leading cause of morbidity and mortality among children under five, particularly in low and middle-income countries. In 2020, the Under-Five Mortality Rate for ARI was 34 per 1.000 children, while the Infant Mortality Rate for ARI was 38 per 1.000 children. This study used a quantitative method with a case-control approach. The subject size in the study was 62, consisting of 31 cases and 31 controls, using the total sampling technique. The results of this study showed that the immunization status variable had an OR value of 41,538; 95% CI: 5,005-344,760 and a p-value of 0,00. The mother's knowledge status had an OR value of 102,857; 95% CI: 11,827-894,522 and a p-value of 0,000. Meanwhile, family smoking behavior showed an OR value of 14,175; 95% CI: 3,893-51,607 and a p-value of 0,000. Therefore, it can be concluded that immunization status, maternal knowledge, and family smoking behavior have a significant influence on the incidence of ARI (Acute Respiratory Infection) in toddlers at Taraweang Health Center.